Altered Functional Mitochondrial Protein Levels in Plasma Neuron-Derived Extracellular Vesicles of Patients With Gadolinium Deposition - Goetzl, Edward J.; Maecker, Holden T.; Rosenberg-Hasson, Yael; Koran, Lorrin M. (Frontiers in Toxicology, 2022)
The retention of the heavy metal, gadolinium, after a Gadolinium-Based Contrast Agent-assisted MRI may lead to a symptom cluster termed Gadolinium Deposition Disease. Little is known of the disorder’s underlying pathophysiology, but a recent study reported abnormally elevated serum levels of pro-inflammatory cytokines compared to normal controls. As a calcium channel blocker in cellular plasma and mitochondrial membranes, gadolinium also interferes with mitochondrial function. We applied to sera from nine Gadolinium Deposition Disease and two Gadolinium Storage Condition patients newly developed methods allowing isolation of plasma neuron-derived extracellular vesicles that contain reproducibly quantifiable levels of mitochondrial proteins of all major classes. Patients’ levels of five mitochondrial functional proteins were statistically significantly lower and of two significantly higher than the levels in normal controls. The patterns of differences between study patients and controls for mitochondrial dynamics and mitochondrial proteins encompassing neuronal energy generation, metabolic regulation, ion fluxes, and survival differed from those seen for patients with first episode psychosis and those with Major Depressive Disorder compared to their controls. These findings suggest that mitochondrial dysfunction due to retained gadolinium may play a role in causing Gadolinium Deposition Disease. Larger samples of both GDD and GSC patients are needed to allow not only testing the repeatability of our findings, but also investigation of relationships of specific mitochondrial protein deficiencies or excesses and concurrent cytokine, genetic, or other factors to GDD’s neurological and cognitive symptoms. Studies of neuronal mitochondrial proteins as diagnostic markers or indicators of treatment effectiveness are also warranted.